Accompany in Times of Pandemic - Trujillo Ríos, John Edward (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2021)
Since the beginning of the pandemic caused by SARS-CoV-2, the measures to prevent this new coronavirus have consisted mainly of social distancing and confinement, these guidelines that have been a great challenge for spiritual accompaniment. Fear and anxiety have appeared strongly due to this global event, which calls for a new form of help. Under these circumstances, the question arises: how to carry out a ministry of support when precisely we must lock ourselves up to avoid more infections? In this work, from pastoral theology, it's intended to elaborate some proposals to answer this question that involves creativity and adaptation.